2013
DOI: 10.4236/jmmce.2013.11003
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Al6061-Frit Particulate Metal Matrix Composites in Sodium Chloride Solution

Abstract: In this investigation, an attempt has been made to develop Al6061-Frit particulate metal matrix composites through stir casting technique using metal molds and to study the corrosion behaviour. Pre heated frit particles were added to matrix as reinforcement. Al6061 containing 2 wt% to 8 wt% in steps of 2 wt% of frit particulate composites were prepared. Corrosion tests were conducted by using Potentiostat model SEP238C where 3.5% NaCl solution was used as corrodent. The corrosion rate of metal matrix composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The heat treated composite material shown higher corrosion resistance when compared to untreated composite material [23]. The increased percentage of frit in the Al6061 matrix shown increased corrosion resistance and corrosion rate of heat-treated composites found lower than untreated composites [24]. The results of the experiments shown that when the material was subjected to overloads and corrosive environment the fatigue life reduced due to corrosion pit formation, anodic dissolution and hydrogen embrittlement [25].…”
Section: Introductionmentioning
confidence: 98%
“…The heat treated composite material shown higher corrosion resistance when compared to untreated composite material [23]. The increased percentage of frit in the Al6061 matrix shown increased corrosion resistance and corrosion rate of heat-treated composites found lower than untreated composites [24]. The results of the experiments shown that when the material was subjected to overloads and corrosive environment the fatigue life reduced due to corrosion pit formation, anodic dissolution and hydrogen embrittlement [25].…”
Section: Introductionmentioning
confidence: 98%
“…Al6061 has been commonly used as base metal for aluminium metal matrix composites (AMCs) reinforced with a variety of reinforcements. Dasappa Ramesh et al [1] reported corrosion behaviour of Al6061 alloy and Al6061 reinforced with frit particulates in acid medium. Corrosion tests were performed with 3.5% NaCl solution as corrodent using Potentiostat model SEP238C.…”
Section: Introductionmentioning
confidence: 99%